A novel Bruton tyrosine kinase gene variation was found in an adult with X‐linked agammaglobulinemia during blood cross‐matching prior to surgical operation. Issue 5 (22nd May 2019) - Wang, N.; Tian, Y.; Jia, S.; Shao, L.; Yu, W.; Fang, M.
SUMMARY: Aims/Objectives: To investigate the underlying molecular mechanism of the patient's ABO typing discrepancy. Background: ABO typing discrepancy was frequently seen in patients due to different causes. In this study, ABO typing discrepancy was found in a 24‐year‐old man with arthralgia, whose forward ABO grouping was O and reverse ABO grouping was AB. Primary immunodeficiency disease was speculated in this patient, especially X‐linked agammaglobulinemia (XLA). Methods: Immunoglobulins of all isotypes were detected using a specific protein analyser. Lymphocyte subgroups were analysed by flow cytometry. All 19 exons and boundaries of BTK gene were amplified by polymerase chain reaction (PCR), and all PCR products were sequenced by a DNA analyser. BTK protein in the leukocytes and platelets was detected by Western blot. Results: No B lymphocytes could be detected in the peripheral blood of the patient. A novel BTK gene variation, c.817G>T, in the exon 9 of BTK gene was discovered. No BTK protein expression could be detected in the leukocytes and platelets of the patient. Conclusions: XLA could be occasionally discovered by ABO typing discrepancy in some cases because of the deficiency of reciprocal IgM anti‐A and/or anti‐B antibodies in the serum of the patient. Humoral immunodeficiency is one of the causes of ABO typing discrepancy.